Forests, water, and people in the humid tropics : past, present, and future hydrological research for intergrated land and water management - Bonell, Michael; Bruijnzeel, Leendert Adriaan; International Hydrological Programme; International Union of Forestry Research Organisation (Cambridge, UK : Cambridge University Press, 2005)
09